Application of permeability‐limited physiologically‐based pharmacokinetic models: Part II ‐ prediction of p‐glycoprotein mediated drug–drug interactions with digoxin. Issue 9 (19th May 2013) - Neuhoff, Sibylle; Yeo, Karen Rowland; Barter, Zoe; Jamei, Masoud; Turner, David B.; Rostami‐Hodjegan, Amin; Nakashima, Emi; Brouwer, Kim; Hammarlund‐Udenaes, Margareta; Terasaki, Tetsuya
Abstract Digoxin is the recommended substrate for assessment of P‐glycoprotein (P‐gp)‐mediated drug–drug interactions (DDIs) in vivo. The overall aim of our study was to investigate the inhibitory potential of both verapamil and norverapamil on the P‐gp‐mediated efflux of digoxin in both gut and liver. Therefore, a physiologically‐based pharmacokinetic (PBPK) model for verapamil and its primary metabolite was developed and validated through the recovery of observed clinical plasma concentration data for both moieties and the reported interaction with midazolam, albeit a cytochrome P450 3A4‐mediated DDI. The validated inhibitor model was then used in conjunction with the model developed previously for digoxin. The range of values obtained for the 10 trials indicated that increases in area under the plasma concentration‐time curve (AUC) profiles and maximum plasma concentration observed (Cmax) values of digoxin following administration of verapamil were more comparable with in vivo observations, when P‐gp inhibition by the metabolite, norverapamil, was considered as well. The predicted decrease in AUC and Cmax values of digoxin following administration of rifampicin because of P‐gp induction was 1.57‐ (range: 1.42–1.77) and 1.62‐fold (range: 1.53–1.70), which were reasonably consistent with observed values of 1.4‐ and 2.2‐fold, respectively. This study demonstrates the application of permeability‐limited models of absorption and distribution within a PBPK framework together with relevant in vitro data on transporters to assess the clinical impact of modulated P‐gp‐mediated efflux by drugs in development. © 2013 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 102:3161–3173, 2013